Intravitreal Bevacizumab in vascular pigment epithelium detachment as a result of subfoveal occult choroidal neovascularization in age-related macular degeneration - Ach, Thomas; Höh, Alexandra E.; Ruppenstein, Mira Katharina; Kretz, Florian T. A.; Dithmar, Stefan (Retina, 2010)
Purpose: - The purpose of this study was to evaluate the effect of intravitreally administered bevacizumab on untreated vascularized pigment epithelium detachment (PED) in sub- or juxtafoveal occult choroidal neovascularization as a result of age-related macular degeneration. - Methods: - In this retrospective study, 28 untreated eyes of 26 patients (4 men, 22 women; mean age, 74.6 ± 7.2 years) with PED and sub- or juxtafoveal occult choroidal neovascularization as a result of age-related macular degeneration and additional intra- and/or subretinal fluid were treated with intravitreal injections of 1.25 mg bevacizumab. Baseline and follow-up visits included best-corrected visual acuity, complete ophthalmic examination, and Stratus optical coherence tomography. Fluorescein angiography was performed at baseline. Reinjections were performed if intra- and/or subretinal fluid persisted or recurred or PED increased. - Results: - Patients received 3.2 ± 1.8 injections (follow-up 37.9 ± 18.3 weeks). Mean maximum PED height showed a tendency to decrease (372 ± 150.5 μm to 290.3 ± 189 μm; P = 0.094). In 14 eyes (53.8%), PED height was reduced at last visit, including complete flattening in 1 eye. Mean visual acuity remained stable (0.58 ± 0.30 logarithm of the minimum angle of resolution to 0.58 ± 0.37 logarithm of the minimum angle of resolution; P = 0.905). Pigment epithelium detachment response to treatment did not correlate with baseline PED height or visual acuity at baseline or at the last visit. One patient sustained a retinal pigment epithelium rip, and another patient sustained an extensive subretinal hemorrhage. - Conclusion: - During bevacizumab therapy, mean PED height decreases in 50% of patients. No predictive factors for the response of PED to bevacizumab treatment could be identified. Treatment of PED with bevacizumab might result in a long-term functional benefit compared with the natural course.